A low-cost, tablet-based option for prehospital neurologic assessment: The iTREAT Study. (5th July 2016) - Chapman Smith, Sherita N.; Govindarajan, Prasanthi; Padrick, Matthew M.; Lippman, Jason M.; McMurry, Timothy L.; Resler, Brian L.; Keenan, Kevin; Gunnell, Brian S.; Mehndiratta, Prachi; Chee, Christina Y.; Cahill, Elizabeth A.; Dietiker, Cameron; et al.
Abstract : Objectives: In this 2-center study, we assessed the technical feasibility and reliability of a low cost, tablet-based mobile telestroke option for ambulance transport and hypothesized that the NIH Stroke Scale (NIHSS) could be performed with similar reliability between remote and bedside examinations. Methods: We piloted our mobile telemedicine system in 2 geographic regions, central Virginia and the San Francisco Bay Area, utilizing commercial cellular networks for videoconferencing transmission. Standardized patients portrayed scripted stroke scenarios during ambulance transport and were evaluated by independent raters comparing bedside to remote mobile telestroke assessments. We used a mixed-effects regression model to determine intraclass correlation of the NIHSS between bedside and remote examinations (95% confidence interval). Results: We conducted 27 ambulance runs at both sites and successfully completed the NIHSS for all prehospital assessments without prohibitive technical interruption. The mean difference between bedside (face-to-face) and remote (video) NIHSS scores was 0.25 (1.00 to −0.50). Overall, correlation of the NIHSS between bedside and mobile telestroke assessments was 0.96 (0.92–0.98). In the mixed-effects regression model, there were no statistically significant differences accounting for method of evaluation or differences between sites. Conclusions: Utilizing a low-cost, tablet-based platform and commercial cellular networks, we can reliably perform prehospital neurologic assessments in both rural and urban settings. Further research is needed to establish the reliability and validity of prehospital mobile telestroke assessment in live patients presenting with acute neurologic symptoms.